Enhancing Patient Outcomes through Collaborative Care: The Role of Physical Therapists, Phlebotomists, and Lab Technicians - Alalwan, Fatimah Mohammed; Al Sahwan, Fatimah Abdullah; Alzouri, Yasmin Habib; AlSles, Wajeeha Abdulmohsen; Alqattan, Heba Saeed; Al Hayik , Zainab Mahdi; Alshomimi, Zainab Zakaria; ALAbbas, Mathani Abdullah (Journal of Ecohumanism, 2024)
Introduction: Collaborative care is an important strategy for improving patient outcomes in modern healthcare. Patient centered care can be more efficient, comprehensive, and more effective when the knowledge of multiple healthcare professional is integrated. Physical therapists, phlebotomists, and lab technicians are the important contributors to this multidisciplinary model. Combined efforts are made to doubtlessly diagnose, treat and recover at the peak, all for the betterment of patients’ healthcare experience. Aim of work: To explore the impact of collaborative care on patient outcomes by examining the roles of physical therapists, phlebotomists, and lab technicians in healthcare settings. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Enhancing, Patient Outcomes, Collaborative Care, Role, Physical Therapists, Phlebotomists, and Lab Technicians. The search was restricted to publications from 2016 to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: In modern healthcare settings it is essential for patient outcomes that there is collaborative care among physical therapist, phlebotomist and lab technicians. Each professional brings a unique contribution to the diagnostic and therapeutic and process of monitoring of patient safety, effective treatment and improved quality of life. Better communication between doctors and nurses, bringing in new technologies, and interprofessional education that supplements this can best fit professional’s roles within healthcare systems to provide better patient care. Efficient delivery of healthcare will be achieved by addressing challenges to each group to strengthen their collaboration